Boom town music education : a co-creating way to learn music within formal music education - Gullberg, Anna-Karin (Luleå tekniska universitet, Musik och dans, 2006)
The general purpose of this presentation is to discuss how alternative forms of learning strategies in exclusively designed contexts may strengthen the development of musical, social and personal competences. Research in music education has confirmed that how knowledge in music is created is highly correlated with context qualities, as for example the organization of musical learning and social interaction. Still, it is difficult to free the practice of learning in music from conservatoire tradition and didactic "hidden curricula's". Formal learning situations means benefiting from experienced teachers and mentors, but music institutions all too often suffer by institutionalization and a levelling of cultures. On the other hand informal music learning is largely characterised by co-creating and peer learning. By not paying sufficient attention to learning processes within smaller groups, the great opportunities for powerful growth in personal and social skills, are also passed over.In the autumn of 2005, a completely new curriculum in music education - BoomTown Music Education (BTME) - was born within the School of Music in Piteå but as a branch of the municipal music project BoomTown in Borlänge. The educational baseline is resting on scientific theories and previous research dealing with informal learning strategies. Peer learning and playing by the ear is here acknowledged and strongly supported. The philosophy of BTME opens up to a wider musical, social and ethnic variety and is supported by a mixture of guest musicians, artists, innovators etc. Several research projects are started, and data is already collected by observations during rehearsals and concerts. An interesting body of knowledge will also come from student's diaries and written reflections, collected since the start. Research results will in time contribute with important knowledge about how learning in music is affected by the organisation and design of learning contexts. Godkänd; 2006; 20070505 (ysko)